2019
DOI: 10.3390/agronomy9060311
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Agronomic Strategies for Enhancing the Yield and Nutritional Quality of Wild Tomato, Solanum Lycopersicum (l) Var Cerasiforme Mill

Abstract: Urbanization and global climate change have constrained plant development and yield. Utilization of wild gene pool, together with the application of sustainable and eco-friendly agronomic crop improvement strategies, is being focused on to tackle mounting food insecurity issues. In this aspect, the green seaweed, Ulva flexuosa, was assessed for plant biostimulant potential on cherry tomato, in terms of seed priming effects, nutrition and yield. SEM-EDX analysis of U. flexuosa presented the occurrence of cell w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 55 publications
1
14
0
1
Order By: Relevance
“…The positive influence of biological fertilizers on the content of polyphenols has also been demonstrated in species such as tomatoes [44,45] or peppers [46][47][48].…”
Section: Treatment P-coumaricmentioning
confidence: 91%
“…The positive influence of biological fertilizers on the content of polyphenols has also been demonstrated in species such as tomatoes [44,45] or peppers [46][47][48].…”
Section: Treatment P-coumaricmentioning
confidence: 91%
“…The most important factor in these is the priming agent, which can be either water or chemical. Depending on the priming agent, this enhancement technique can be done as hydro priming, osmo priming, bio priming, hormone priming, thermal priming, or solid matrix priming [2,28,29,[32][33][34][35][36][37]. The key factors in this procedure are the imbibition time and osmotic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has already shown the potential of resistance inducers, such as methyl salicylate, to increase the seedling emergence and plant growth in different cultivars of rice, however, with a dose-dependent effect in relation to cultivars [17]. In addition, the use of environmentally friendly bio-fertilisers, such as algae extracts, improve plant development, with an increase in germination and seedling vigour [3,4] and in the levels of phenols and ascorbic acid [3]. The fact that uninoculated potential elicitors-treated beetroots had similar or poorer vegetative development than untreated plants can be explained by the energy expended to activate defence mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, some environmentally friendly practices that improve the nutritional status of the plant, can favour the vegetative development and, consequently, minimise the damage caused by pathogens, allowing greater absorption of nutrients and gain in productivity [4,5,16]. Furthermore, due to the recent restrictions on the use of chemical nematicides and the lack of effective alternatives for nematode control, extensive research has been conducted in an effort to find novel control strategies.…”
Section: Introductionmentioning
confidence: 99%